2014
DOI: 10.1088/0004-637x/782/2/102
|View full text |Cite
|
Sign up to set email alerts
|

XMM-NEWTONANDCHANDRAOBSERVATIONS OF THE EJECTA-DOMINATED MIXED-MORPHOLOGY GALACTIC SUPERNOVA REMNANT G352.7–0.1

Abstract: We present a spatial and spectral X-ray analysis of the Galactic supernova remnant (SNR) G352.7−0.1 using archival data from observations made with the XMM-Newton X-ray Observatory and the Chandra X-ray Observatory. Prior X-ray observations of this SNR had revealed a thermal center-filled morphology that contrasts with a shell-like radio morphology, thus establishing G352.7−0.1 as a member of the class of Galactic SNRs known as mixedmorphology SNRs (MMSNRs). Our study confirms that the X-ray emission comes fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 63 publications
1
12
0
Order By: Relevance
“…However, XMM-Newton image of the SNR showed that the X-ray emission completely fills the interior of the radio remnant; therefore, Giacani et al (2009) concluded that this remnant belonged to the MM class. Pannuti et al (2014) confirmed that this SNR is MM by using XMM-Newton and Chandra data. MM SNRs (Rho & Petre 1998), also known as thermal composites, are identified with shell emission in the radio band and centrally brightened thermal emission in the X-ray band with little or no limb brightening.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…However, XMM-Newton image of the SNR showed that the X-ray emission completely fills the interior of the radio remnant; therefore, Giacani et al (2009) concluded that this remnant belonged to the MM class. Pannuti et al (2014) confirmed that this SNR is MM by using XMM-Newton and Chandra data. MM SNRs (Rho & Petre 1998), also known as thermal composites, are identified with shell emission in the radio band and centrally brightened thermal emission in the X-ray band with little or no limb brightening.…”
Section: Resultssupporting
confidence: 57%
“…Recently, Pannuti et al (2014) presented X-ray study of the remnant by using data from XMM-Newton and Chandra. Their XMM-Newton spectra gave the bestfit with a single thermal component (kT e ∼ 1.2 keV) in NEI condition with enhanced abundances of Si and S. On the other hand, their Chandra spectra has been best described with two thermal components (VNEI+VNEI) with temperatures of ∼2.14 keV for hard and ∼0.39 keV for soft component for the whole remnant, although the spectra of some regions can be fit with single VNEI model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetrically, it can not excluded that some CC SNRs are found at the low ionisation end. Part of SNR G15.9+0.2, for instance, still has emission at 6.4 keV, while SNR G352.7−0.1 has an Fe K centroid at 6.44 keV and is also of uncertain type; some studies suggest that it is the remnant a CC SNR (Giacani et al 2009;Pannuti et al 2014). Another caveat is that the current sample of Fe K emitting objects inherently contains some age bias, the youngest objects being preeminently of type Ia.…”
Section: Evolution Of Fe K Lines In Snrsmentioning
confidence: 99%
“…In Kes 41, the dust destruction scenario may not be favorable because argon, obviously enriched, is an inert element and cannot be easily depleted into dust. In the most recent X-ray studies of G352.7−0.1 and W51C, metal enrichment is explained to come from supernova ejecta (Pannuti et al 2014a;Sasaki et al 2014).…”
Section: Metal Enrichmentmentioning
confidence: 99%